Effect of Minimally Invasive Surfactant Therapy Versus Sham Treatment on Death or Bronchopulmonary Dysplasia in Preterm Infants With Respiratory Distress Syndrome The OPTIMIST: A Randomized Clinical Trial. Issue 3 (24th September 2022) - Dargaville, P.A.; Kamlin, O.F.; Orsini, F.; Wang, X.; De Paoli, A.G.; Kanmaz Kutman, H.G.; Cetinkaya, M.; Aiyappan, A.; Lemyre, B.; Kuo, S.; Rajadurai, V.S.; O'Shea, J.; et al.
Abstract : ( JAMA . 2021;326:2478–2487) Continuous positive airway pressure (CPAP) is recommended for newly born preterm infants. A previous meta-analysis of clinical trials compared CPAP to intubation and ventilation in terms of death or bronchopulmonary dysplasia and found CPAP had a relative risk of 0.91 [95% confidence interval (CI), 0.84-0.99]. In the studies used in meta-analysis, exogenous surfactant was administered only to infants with relatively high levels of inspired oxygen. This study, the OPTIMIST-A trial aimed to determine whether minimally invasive surfactant therapy, using a thin catheter, would lower the incidence of death and/or bronchopulmonary dysplasia.